Laboratory‐based measures of temperature preference and metabolic thermal sensitivity provide insight into the habitat utilisation of juvenile California horn shark (Heterodontus francisci) and leopard shark (Triakis semifasciata). Issue 4 (6th February 2023) - Skelton, Zachary R.; Prinzing, Tanya S.; Hastings, Philip A.; Wegner, Nicholas C.
Abstract: Laboratory‐based studies examining fish physiological and behavioural responses to temperature can provide important insight into species‐specific habitat preferences and utilisation, and are especially useful in examining vulnerable life stages that are difficult to study in the wild. This study couples shuttle box behavioural experiments with respirometry trials to determine the temperature preferences and metabolic thermal sensitivity of juvenile California horn shark ( Heterodontus francisci ) and leopard shark ( Triakis semifasciata ). As juveniles, these two species often occupy similar estuarine habitats but display contrasting behaviours and activity levels – H. francisci are relatively sedentary, whereas T. semifasciata are more active and mobile. This study shows that juvenile H. francisci and T. semifasciata have comparable thermal preferences and occupy similar temperature ranges, but H. francisci metabolism is more sensitive to acute changes in temperature as expressed through a higher Q 10 ( H. francisci = 2.58; T. semifasciata = 1.97; temperature range: 12–24°C). Underlying chronic temperature acclimation to both warm (21°C) and cool (15°C) representative seasonal temperatures did not appear to significantly affect these parameters . These results are discussed in the context of field studies examining known distributions, habitat and movement patterns of H. francisci and T. semifasciata to better understand the role of temperature in species‐specific behaviour. Juvenile H. francisci likely target thermally stable environments, such as estuaries that are close to their preferred temperature, whereas juvenile T. semifasciata metabolism and behaviour appear less dependent on temperature.